2009 International Conference on Computational Science and Engineering 2009
DOI: 10.1109/cse.2009.237
|View full text |Cite
|
Sign up to set email alerts
|

Social Inference Risk Modeling in Mobile and Social Applications

Abstract: Abstract-The emphasis of emerging mobile and Web 2.0 applications on collaboration and communication increases threats to user privacy. A serious, yet under-researched privacy risk results from social inferences about user identity, location and other personal information. In this paper, after analyzing the social inference problem theoretically, we assess the extent of the risk to users of computer-mediated communication and location based applications through 1) a laboratory experimentation, 2) a mobile phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The results suggested that Method 2 was almost as accurate as Method 3 in the realm of computer-mediated communication and proximity-based applications [11,28]. This means that context and community of users allows to effectively model background knowledge for a specific context.…”
Section: Social Inference Risk Prediction Frameworkmentioning
confidence: 97%
See 4 more Smart Citations
“…The results suggested that Method 2 was almost as accurate as Method 3 in the realm of computer-mediated communication and proximity-based applications [11,28]. This means that context and community of users allows to effectively model background knowledge for a specific context.…”
Section: Social Inference Risk Prediction Frameworkmentioning
confidence: 97%
“…More details on calculating the conditional probabilities and information entropy can be found in [11,28] where the authors also set thresholds for information entropy based on users' preferences. If the information entropy is lower than its threshold, there is a high inference risk.…”
Section: Social Inference Risk Prediction Frameworkmentioning
confidence: 99%
See 3 more Smart Citations